2020
DOI: 10.1097/ccm.0000000000004460
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of P25/30 Cortical Somatosensory Evoked Potential Amplitude After Cardiac Arrest*

Abstract: Objectives: The aim of this study was to evaluate the prognostic performance of the peak amplitude of P25/30 cortical somatosensory evoked potentials in predicting nonawakening in targeted temperature management-treated cardiac arrest patients. Design: Prospective analysis. Setting: Four academic tertiary care hospitals. Patients: Eighty-seven cardiac arrest surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…They conclude that their results “indicate that a P25/30 amplitude less than 0.45 µV is a reliable threshold below which no patients recover consciousness.” We would like to comment. Whereas the results by Oh et al (1) are interesting and call for further investigation of the benefits of their strategy, their conclusion stating a 100% specificity seems currently unwarranted. Although the false positive rate (FPR) of absent early cortical SSEP for predicting poor outcome has usually been estimated to be within the 0.4–0.7% range (2), a recent reevaluation of this value rose the estimated FPR to an alarming 7.7% by taking the “self-fulfilling prophecy” (SPF) bias into account (2).…”
Section: To the Editormentioning
confidence: 97%
See 3 more Smart Citations
“…They conclude that their results “indicate that a P25/30 amplitude less than 0.45 µV is a reliable threshold below which no patients recover consciousness.” We would like to comment. Whereas the results by Oh et al (1) are interesting and call for further investigation of the benefits of their strategy, their conclusion stating a 100% specificity seems currently unwarranted. Although the false positive rate (FPR) of absent early cortical SSEP for predicting poor outcome has usually been estimated to be within the 0.4–0.7% range (2), a recent reevaluation of this value rose the estimated FPR to an alarming 7.7% by taking the “self-fulfilling prophecy” (SPF) bias into account (2).…”
Section: To the Editormentioning
confidence: 97%
“…We have read with great interest the article published in a recent issue of Critical Care Medicine by Oh et al (1) who conclude that currently somatosensory evoked potentials (SSEPs) are considered robust tests that are relatively insensitive to some confounders after cardiac arrest who received targeted temperature management (1). Elaborating their strategy on previous work shows that all patients showing low (< 0.62 µV) N20-P25/30 amplitudes had poor outcomes, they focused on baseline-to-P25/30 amplitudes, considered to be less prone to bias due to suboptimal electrode positioning (1). By resorting to that strategy, they obtained an improved (86.4%) sensitivity of abnormal early SSEP for predicting poor outcome, without compromising specificity.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…In 21 studies, when bilateral absence of N20 waves was observed in the SSEP conducted at 24 hours or more after ROSC, a poor neurological outcome was predicted with specificity of 50% to 100% and sensitivity of 18.2% to 70.5%. 101,102,114,121,123,127,128,134,[144][145][146][147][148][149][150][151][152][153][154][155][156] Although decrease in the amplitude of N20 is associated with a poor neurological outcome in some studies, further studies are needed. 152,155,157,158 Since there is a high likelihood that results are affected by confounding factors within 24 hours after ROSC, it is recommended to use bilateral absence of N20 waves more than 24 hours after ROSC in combination with other prognostic tests.…”
Section: Electrophysiology Ssepmentioning
confidence: 99%